Firm-specific information, analysts' superiority and investment value - Lu Li; Erjia Yang; Tusheng Xiao (China Journal of Accounting Research, 2014)
Using a sample of Chinese security analysts' recommendations from 2005 to 2010, we examine the source of analysts' superiority and the investment value of their recommendations. Using a calendar-time portfolio approach, we find that, on average, analysts' recommendations are valuable and that analysts are better at analyzing and transferring firm-specific information than market-wide or industry-level information. In addition, we show that the investment value of recommendations increases as firm-specific information becomes more important in stock pricing. Our empirical results are useful in guiding investors and helping brokerage houses to evaluate the output of research departments.
Keywords: 650; Firm-specific information; Analysts' superiority; Investment value